EFEK ANTIINFLAMASI KOMBINASI ASTAXANTHIN DENGAN VITAMIN E TERHADAP JUMLAH LEUKOSIT Studi Eksperimental pada Tikus Putih Jantan Galur Wistar yang Diinduksi Karagenan - Nafisa Yasmin Suseno (PT. Hasba Edukasi Mandiri, 2026)
Inflammation is a defense mechanism of the body, with leukocyte count serving as a primary indicator. Uncontrolled inflammation contributes to the pathogenesis of various diseases. Carrageenan activates Toll-like receptor 4 (TLR4) and the NF-κB pathway, inducing pro-inflammatory cytokine production and increasing leukocyte counts. Astaxanthin combined with vitamin E has anti-inflammatory properties by inhibiting NF-κB, COX-2, LOX, and reactive oxygen species (ROS). This study aimed to evaluate the anti-inflammatory effect of astaxanthin and vitamin E on leukocyte counts in carrageenan-induced male Wistar rats. This experimental study used a post-test-only control group design with 30 male Wistar rats randomly assigned to three groups: normal control (KN), disease control (KS), and treatment (KP). KN received standard feed and distilled water. KP received astaxanthin (0.72 mg/kg body weight) and vitamin E (24.1 mg/kg body weight). One hour later, KS and KP were injected intraperitoneally with 0.1 mL of 1% carrageenan and observed for 24 hours. Blood samples were collected from the orbital sinus, and leukocyte counts were measured using a hematology analyzer. Data were analyzed using Kruskal–Wallis and post hoc Mann–Whitney tests. Mean leukocyte counts were 5.82 × 10³/μL (KN), 12.23 × 10³/μL (KS), and 7.63 × 10³/μL (KP). The Kruskal–Wallis test showed a significant difference among groups (p < 0.05), confirmed by post hoc analysis (p < 0.05). The combination of astaxanthin and vitamin E significantly reduced leukocyte counts, indicating an anti-inflammatory effect in carrageenan-induced male Wistar rats.